Synthesis and Photocatalytic Activities of Ionic Liquid Assisted Preparation of TiO2 Nanoparticles - Dai, J.; Hi, R.; Wang, W.; Fang, D. (Asian Journal of Chemistry, 2012)
The well-crystallized anatasetitania nanoparticles were synthesized by one-step routes under low-temperature using room temperature ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM][BF4]) as an additional solvent with water. The photocatalytic properties of TiO2 nanoparticles were evaluated by photocatalytic degradation experiments of methyl orange. The TiO2-ionic liquid nanoparticles still hold a high photocatalytic activity after the catalyst was recycled 9 times. The TiO2 nanoparticles show a higher photocatalytic activity than the TiO2 with pure water and commercial TiO2 (P25), which may be related to the high crystallinity, the pure anatase phase, small size and the enhanced absorbability associated with the existence of [BMIM][BF4].